Crescimento de recém-nascidos pré-termo de muito baixo peso durante internação em Unidade de Terapia Intensiva neonatal e fatores associados - Altermann, Carolina Santos (2016)
The very low birth weight infants are a high risk population, because of their immaturity and diseases caused by this condition. The growth of the infants significantly influences morbidity and mortality, and are associated with factors such as the clinical outcome, ventilatory support, conditions at birth and received nutritional support. The nutritional goal of preterm is seeking a similar growth Intrauterine occurred in the same gestational age, without causing either deficiency, such as excessive nutrient supply. However, there may be metabolic and absorptive difficulties to reach their daily needs, exposing most of these children to a delay in growth after birth. This is a descriptive research, conducted retrospective longitudinal with secondary data of very low birth weight infants during the hospitalization in Neonatal Intensive Care Unit (NICU) of University Hospital of Santa Maria, between 2010 and 2014. The objectives of this study were to evaluate the growth, by weight, length and head circumference, nutritional supply during hospitalization, clinical and birth conditions, and to identify factors associated with growth failure at NICU discharge. There was a high incidence of growth failure (63,8 %) in very low birth weight infants, during the stay in NICU. During the period, the weight was the most affected anthropometric measure, followed by length, and lastly the head circumference. The average observed weekly caloric offer did not reached the recommended nutritional goals, the incidence of bronchopulmonary dysplasia was high and other conditions were within expectations. In this study, the main risk factors for growth failure, in very low birth weight infants, at NICU discharge, were the increase in mechanical ventilation and born small for gestational age, which means, present intrauterine growth restriction. This study is of great value to the institution, because knowing the profile and the growth pattern of very low birth weight infants hospitalized, as well as nutritional practices, will contribute to the improvement of care practices in place, and, will contribute to the continuous improvement of quality of service in the National Health System.